Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
In order to solve by elimination we first need to find a common multiple of the x or y values. Lets eliminate x. 7 and 2 (both the x values) can both go into 14 without having any left over. In order to turn 7 into 14 we must multiply it by 2. But in this case, we'll multiply the entire equation by 2 in order to not change its value.
14x-4y=34
Now lets do the same for the second equation. In order to turn 2 into 14, we can multiply it by 7, but again we need to multiply the entire equation by 7 so we dont change it's value.
14x+49y=511
Now that we have the same coefficient on both the x's we can get rid of them by subtracting the two equations.
14x+49y=511
14x-4y=34
53y=477
y=9
Now that we have the value for y we can plug it in and solve for x.
7x-2(9)=17
7x-18=17
7x=35
x=5
The value of y is 9 and the value of x is 5.
14x-4y=34
Now lets do the same for the second equation. In order to turn 2 into 14, we can multiply it by 7, but again we need to multiply the entire equation by 7 so we dont change it's value.
14x+49y=511
Now that we have the same coefficient on both the x's we can get rid of them by subtracting the two equations.
14x+49y=511
14x-4y=34
53y=477
y=9
Now that we have the value for y we can plug it in and solve for x.
7x-2(9)=17
7x-18=17
7x=35
x=5
The value of y is 9 and the value of x is 5.
7x - 2y = 17 .....(i)
2x + 7y = 73......(ii)
Let us eliminate x, multiply equation (i) by 2 and (ii) by 7.
7x - 2y = 17 .....(i) x2
2x + 7y = 73......(ii) x7
2(7x - 2y) = 2(17)
14x - 4y = 34.....(iii)
7(2x + 7y) = 7(73)
14x + 49y = 511 ....(iv)
14x - 4y = 34..........(iii)
14x + 49y = 511 ....(iv)
We can now eliminate x by (iii) - (iv)
(14x - 4y) - (14x + 49y) = 34 - 511
14x - 4y -14x - 49y = -477
14x - 14x - 4y - 49y = -477
0x -53y = -477
- 53y = - 477.
y = - 477/-53. Use your calculator.
y = 9.
Now we can now substitute y = 9 in equation (i)
7x - 2y = 17, Recall y = 9
7x - 2(9) = 17
7x - 18 = 17
7x = 17 + 18
7x = 35
x = 35/7 = 5.
Therefore, x = 5, y = 9. Cheeeerrs!
2x + 7y = 73......(ii)
Let us eliminate x, multiply equation (i) by 2 and (ii) by 7.
7x - 2y = 17 .....(i) x2
2x + 7y = 73......(ii) x7
2(7x - 2y) = 2(17)
14x - 4y = 34.....(iii)
7(2x + 7y) = 7(73)
14x + 49y = 511 ....(iv)
14x - 4y = 34..........(iii)
14x + 49y = 511 ....(iv)
We can now eliminate x by (iii) - (iv)
(14x - 4y) - (14x + 49y) = 34 - 511
14x - 4y -14x - 49y = -477
14x - 14x - 4y - 49y = -477
0x -53y = -477
- 53y = - 477.
y = - 477/-53. Use your calculator.
y = 9.
Now we can now substitute y = 9 in equation (i)
7x - 2y = 17, Recall y = 9
7x - 2(9) = 17
7x - 18 = 17
7x = 17 + 18
7x = 35
x = 35/7 = 5.
Therefore, x = 5, y = 9. Cheeeerrs!
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.